2015
DOI: 10.1002/cite.201500143
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Influence on the Hydrodeoxygenation of Guaiacol over Pt/SiO2 and Pt/H‐MFI 90 Catalysts

Abstract: Second generation biofuels are produced in the bioliq process at the Karlsruhe Institute of Technology via gasification of pyrolysis oil and synthesis of gasoline from the emerging synthesis gas. An alternative strategy is the direct upgrading of the pyrolysis oil by hydrodeoxygenation (HDO). The present study reports on the HDO of guaiacol as one of the phenolic compounds strongly abundant in such mixtures. Special focus was laid on the solvent influence using Pt-based catalysts. Higher HDO ability was seen u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…This function is mainly found in liquid‐phase HDO batch reactor set‐ups which are rather common for catalytic screening; (3) Acting as co‐reactant. Solvents could participate in HDO reaction through interaction with reactants, catalyst or themselves,, which is commonly found when polar protic solvents are employed.…”
Section: Hydrodeoxygenation Using H2mentioning
confidence: 99%
See 1 more Smart Citation
“…This function is mainly found in liquid‐phase HDO batch reactor set‐ups which are rather common for catalytic screening; (3) Acting as co‐reactant. Solvents could participate in HDO reaction through interaction with reactants, catalyst or themselves,, which is commonly found when polar protic solvents are employed.…”
Section: Hydrodeoxygenation Using H2mentioning
confidence: 99%
“…Compared with non‐polar ether solvent, ethanol and hydrogenated or reduced acetone could form hydrogen bonding with hydroxyl groups existing the bio‐oil, resulting in effective bio‐oil features improvement (including decreasing water content, lower viscosity and increasing heating value) by accelerating the further decomposition of organic compounds into light oil. As for lignin model compounds, the influence of solvent on the performance of guaiacol HDO process over Pt‐based catalyst was investigated by Helliger and co‐workers . Results showed that solvent could affect phase behaviour, solubility of reactant and H 2 as well as the catalyst's stability.…”
Section: Hydrodeoxygenation Using H2mentioning
confidence: 99%
“…Compared with using water as a solvent, the use of a hydrocarbon can omit the separation process of deoxygenated products from water. In addition, the presence of water may block the adsorption of the reactant on the active sites of the catalyst [32].…”
Section: Deoxygenation Of Palm Oilmentioning
confidence: 99%
“…Product selectivities and reaction rates can be strongly influenced by the solvent and the phase distribution of the components in the reaction mixture. [29][30][31] Most publications have focused on vapor-phase HDO to obtain aromatics, [14,15,24,27,28,[32][33][34][35][36][37] perhaps targeting process integration with pyrolysis. [37] Works on liquid-phase HDO have aimed at cyclic aliphatics [16] or, in the case of aqueous systems, at aromatics.…”
Section: Introductionmentioning
confidence: 99%
“…[18,20,39,40] Furthermore, guaiacol HDO in such solvents has been studied extensively with sulfides and noble metal catalysts. [31,[41][42][43][44] Hellinger et al [31] compared the influence of non-polar and oxygenated solvents on guaiacol HDO and found that the alkane solvents promoted high conversion and deoxygenation, as well as low sintering of Pt particles. Supported Pt catalysts have been studied for the HDO of alkylphenols to obtain aromatics in vapor-phase [15,24,28,33] and to some extent in aqueous-phase [21] and in liquid alkane solvents.…”
Section: Introductionmentioning
confidence: 99%